How environmental awareness affects the spatial convergence of urban economic resilience: evidence from China - Li, Yanling; Xiao, Ya (Frontiers in Environmental Science, 2023)
This study utilizes a panel dataset covering 262 Chinese cities from 2012 to 2019 and employs spatial econometric convergence test models to investigate the impact of public environmental awareness on spatial convergence of urban economic resilience. Empirical results reveal a significant spatial convergence pattern in urban economic resilience, but environmental awareness hampers this convergence. Through a mediation analysis, we find that the role of environmental awareness in the spatial convergence of urban economic resilience is moderated by two critical factors: foreign investment and scientific expenditure. The development of foreign investment and an increase in the scale of scientific expenditure weaken the inhibitory effect of environmental awareness on the spatial convergence of urban economic resilience.